Environmental contamination with cytotoxic drugs in 15 hospitals from 11 European countries—results of the MASHA project. Issue 2 (4th April 2020) - Korczowska, Ewelina; Crul, Mirjam; Tuerk, Jochen; Meier, Klaus
Abstract: Background: Evaluating environmental contamination with cytotoxic drugs in hospitals is one of the fundamental requirements to ensure the occupational safety of all healthcare professionals. The European Society of Oncology Pharmacy (ESOP) undertook the first independent, multicenter, pan-European study, involving over a dozen hospitals from 11 different countries, to measure the state of cytotoxic contamination in the workplace. Objective: To obtain an overview of the current situation in European hospitals with regards to cytotoxic drug contamination at various sites, including drug preparation (pharmacy) and administration areas (ward). The secondary objectives are to evaluate the environmental contamination with cytotoxic drugs circulating within a facility known as the hospital medication system (process flow of drug) and to evaluate the impact of changes in local cleaning practices. Materials and methods: The study was carried out at 15 hospitals in Europe evaluating the surface contamination in the preparation and administration areas before (part I) and after (part II and part III) training and the implementation of ESOP cleaning recommendations. Assessment of surface contamination with 11 antineoplastic drugs was performed using wipe samples taken from 10 comparable surfaces (5 each in the preparation and administration areas). These samples were analyzed by liquid chromatography–tandem mass spectrometry. Results: The study demonstrated the presence of surface contamination in preparation and administration areas in all hospitals, with measurable amounts of at least 1 agent detected on sampled surfaces. Before the implementation of the ESOP cleaning recommendations, 324 out of 1595 results were positive (20%). In 11 of 15 hospitals (73%), substances were detected which were not prepared or administrated in the sampling day. After implementation of the ESOP recommendations, only 14% of results were positive (226/1639). Sixty-nine percent of wards (9/13) improved or stayed at the same level in the number of positive samples. The floors on the wards were shown to be the most frequently contaminated (42% of samples were positive). The amount of contamination in the pharmacies was not correlated to the amount of chemotherapy prepared nor to the use of special devices such as closed-system transfer devices. Conclusion: The MASHA study provides an overview of the contamination levels with cytotoxic drugs in European hospitals. Upon implementation of ESOP cleaning recommendations, improvements could be seen, with a reduced number of positive-wipe samples and lower amounts of surface concentration detected. The study demonstrates that improving standard work procedures is able to substantially reduce contamination in the workplace.